MAPPING PRE-SERVICE TEACHERS’ AI LITERACY COMPETENCE BASED ON UNESCO FRAMEWORK: A DESCRIPTIVE STUDY - Fikri Dwi Oktaviani; Gema Rullyana; Linda Setiawati; Liddya Ganda Asmara (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
Artificial Intelligence (AI) literacy competence is an urgent necessity for pre-service teachers in the era of digital transformation. This study aims to map the AI literacy competence of pre-service teachers based on the UNESCO AI Competency Framework for Teachers, encompassing five aspects: Human-Centred Mindset, Ethics of AI, AI Foundations and Applications, AI Pedagogy, and AI for Professional Development. This research employed a descriptive quantitative approach using a survey method. A self-assessment instrument based on a 5-point Likert scale with 75 statement items was distributed online to 252 active students of education study programs in Indonesia during November-December 2025. Pearson validity testing yielded item-total correlations of 0.467 to 0.784, and Cronbach's Alpha produced 0.970, indicating a highly reliable instrument. Results show that students' AI literacy competence falls in the very high category at the Acquire Level, and high at both Deepen and Create levels. Human-Centred Mindset and Ethics of AI consistently achieved the highest scores, while AI for Professional Development showed the lowest at the Create level (M = 3.68). A significant gap exists between the high frequency of AI tool usage (84.5%) and low formal training participation (44.8%). These findings imply the need to redesign the LPTK curricula to systematically integrate AI literacy, contextual and sustainable AI literacy training programs. ABSTRAK Kompetensi literasi kecerdasan buatan (AI) merupakan kebutuhan mendesak bagi mahasiswa calon guru di era transformasi digital. Penelitian ini bertujuan memetakan kompetensi literasi AI mahasiswa calon guru berdasarkan AI Competency Framework for Teachers dari UNESCO yang mencakup lima aspek: Human-Centred Mindset, Ethics of AI, AI Foundations and Applications, AI Pedagogy, dan AI for Professional Development. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan metode survei. Instrumen self-assessment berbasis skala Likert 5 poin dengan 75 butir pernyataan disebarkan secara daring kepada 252 mahasiswa aktif program studi kependidikan di Indonesia pada November-Desember 2025. Uji validitas Pearson menghasilkan korelasi item-total sebesar 0,467 hingga 0,784, dan uji reliabilitas Cronbach's Alpha menghasilkan nilai 0,970. Hasil penelitian menunjukkan bahwa kompetensi literasi AI mahasiswa berada pada kategori sangat tinggi di Level Acquire, dan tinggi di Level Deepen dan Create. Aspek Human-Centred Mindset dan Ethics of AI secara konsisten memperoleh skor tertinggi di seluruh level, sementara AI for Professional Development menunjukkan skor terendah pada Level Create (M = 3,68). Terdapat kesenjangan signifikan antara tingginya frekuensi penggunaan AI (84,5%) dengan rendahnya partisipasi pelatihan formal (44,8%). Temuan ini mengimplikasikan perlunya redesain kurikulum LPTK yang mengintegrasikan literasi AI secara sistematis, dan program pelatihan literasi AI yang kontekstual dan berkelanjutan.